A bibliometric analysis of Malaysian authorship pattern in the field of engineering, 2000 - 2010 - Abdullah, Salmah (Association of Greek Librarians and Information Professionals, 2015)
This paper reports an analysis of publications of scholars affiliated in Malaysia in engineering subject. The study uses bibliometrics method which examines patterns of Malaysian authorship publications in engineering, publish from 2000 to 2010. 11,819 bibliographic records were gathered from Scopus database. The findings indicate Malaysian researchers have considerably enhanced their influence especially since the period of 2007 onwards. Most authors in this field are not one time contributors and 71 authors produced 30 or more papers each. Collaborative research activity has been a consistent trend towards increased collaboration in engineering. The main types of publication produced are conference papers and journal articles. 99.907% of the publications were written in English. This study indicates that Malaysian researchers have made significant contributions to global engineering study